Tinjauan Penggunaan Teknik Kromatografi untuk Memisahkan dan Memurnikan Senyawa Aktif Secara Efisien - Nur Rifa Ashya; Aida Savitri; Annisa Annisa; Difa Az-Zahra; Nurul Hasni Julianti; Shada Adila Abadi; Yumna Zaida (STIKes Ibnu Sina Ajibarang, 2025)
Indonesia boasts an incredible wealth of biodiversity, positioning it as a promising source of natural compounds with significant biological activities. Its flora harbors a wide array of secondary metabolites including alkaloids, flavonoids, phenolic compounds, and terpenoids that hold immense potential for pharmaceutical and health applications. However, to utilize these bioactive molecules effectively, efficient methods for their extraction, separation, and purification are essential. Chromatography techniques such as thin-layer chromatography (TLC), column chromatography, and high-performance liquid chromatography (HPLC) are widely recognized as the most effective approaches for isolating and characterizing these valuable compounds. This article offers a comprehensive review of the existing literature on the chromatographic processes applied in isolating active constituents from medicinal plants. It systematically examines different methodologies adopted for extraction, separation, and identification, critically assessing their strengths and limitations. The review covers how plant materials are prepared, solvents and mobile phases optimized, stationary phases selected, and detection systems employed to achieve high-purity isolates. By comparing outcomes across studies, it illustrates the efficiency of TLC in preliminary screening, the flexibility of column chromatography in bulk separation, and the high resolution and reproducibility offered by HPLC. Results from multiple research efforts demonstrate that these chromatographic techniques can consistently yield pure compounds suitable for further pharmacological testing. The purified isolates not only exhibit potential therapeutic effects but also meet quality standards necessary for development into safe and effective natural medicines. The review highlights best practices in methodology selection, solvent systems, and instrument conditions tailored to specific metabolite classes. Ultimately, this synthesis emphasizes that chromatography plays a pivotal role in unlocking the pharmaceutical potential of Indonesia’s natural biodiversity.